2002
DOI: 10.1046/j.1439-0418.2002.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on some enzymes involved in insecticide resistance in fenitrothion‐resistant and ‐susceptible strains of Musca domestica L. (Dipt, Muscidae)

Abstract: The toxicity of fenitrothion and fenitrothion plus synergists was determined by topical application to adults of fenitrothion‐resistant (571ab) and ‐susceptible (Cooper) strains of Musca domestica L. The strain 571ab was 232‐fold resistant to fenitrothion when compared with the Cooper strain. Co‐administration of fenitrothion with three synergists, namely piperonyl butoxide (PBO), tributylphosphorotrithioate (DEF) and diethyl maleate (DEM) was investigated, respectively, at 1 : 5, 1 : 5 and 1 : 10 ratio. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…There was a significant correlation between all enzyme activity levels and insecticide resistance phenotype by populations. The most probable reason for this, as explained by Ahmed and Wilkins (2002), when an insecticide enters an organism, before reaching its target site, it could meet with different enzyme and protein obstacles and as a result of interactions with these enzymes the insecticide is degraded. The latter results agreed to a large extent with the findings of Bisset et al (2011) who recorded high levels of resistance in all tested strains of the mosquito Aedes aegypti and also they found that resistance ratios were highly correlated with esterase activity (P = 0.00001).…”
Section: Activity Of Glutathione S-transferase (Gst) and Esterases In The Tested Strains Of Culex Pipiensmentioning
confidence: 99%
“…There was a significant correlation between all enzyme activity levels and insecticide resistance phenotype by populations. The most probable reason for this, as explained by Ahmed and Wilkins (2002), when an insecticide enters an organism, before reaching its target site, it could meet with different enzyme and protein obstacles and as a result of interactions with these enzymes the insecticide is degraded. The latter results agreed to a large extent with the findings of Bisset et al (2011) who recorded high levels of resistance in all tested strains of the mosquito Aedes aegypti and also they found that resistance ratios were highly correlated with esterase activity (P = 0.00001).…”
Section: Activity Of Glutathione S-transferase (Gst) and Esterases In The Tested Strains Of Culex Pipiensmentioning
confidence: 99%
“…In general, a slightly higher effect on the rat's liver was recorded in favor of the Imidacloprid pesticide. Ahmed and Wilkins (2001) found that an insecticide-resistant strain of M. domestica has decreased fecundity. Enriquez, et al, (2010) found that the hatching percentage at greater levels of insecticide was found to be lower at the methoxy fenozide LC25 concentration compared to lower concentrations and the control.…”
Section: Fig (9 G1mentioning
confidence: 99%